RAPORT PROCESSING SYSTEM ON VALUE TANGERANG SLTPN 3 USING MICROSOFT VISUAL BASIC 6.0 - Mulyasan Mulyasan; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2005)
Teachers have difficulty in processing student rapport value caused by several thingsincluding: processing still done manually, the value of report cards are processedconsists of many values and the number of students who have calculated the valueraport too much, also serving as a homeroom teacher so that the field of study theynot only deal with one class but also have to teach another class-the class. Thereforewe need a computerized system that can help solve those problems. This system isbuilt using Microsoft Visual Basic 6.0 software, the system begins processing thevalue of report cards from teachers who enter the field of study students' values intothe system, if the teacher is the guardian class so he can fill absences. Then ithomeroom at the end of semester report cards can print reports and report cards to fillthe book also reports legger as reports to the Head of School.